Students’ Preferences for Teaching Methods and their Performances in Schools of Nursing, Nigeria (International Journal of Nursing Education, 2021)
Background: Suboptimal academic performance by the majority of students at higher educationallevel has been linked with ineffective teaching methods by teachers/lecturers.The aim of this study wasto assess teaching methods, academic, and clinical performances among student nurses in schools ofnursing, in North-west Nigeria..Methods: The study adopted a mixed approach of a cross-sectional design.The sample comprises of95 tutors, 31 clinical instructors, 698 students, and the final year students from five selected schools. Anadapted questionnaire was used for data collection. Quantitative data were analyzed using descriptiveand inferential statistic with the aid of IBM SPSS Version 20. The qualitative data were summarizeusing thematic content analysis.Results: Lectures, demonstration, and discussion were the most frequently used methods of instructionin the schools. The average academic performances of students were credit (C). The academicperformance of students in the final examination and Nursing Council Exam was “Pass”. Most ofthe students obtained a C-grade in the clinical examination. The clinical performance rating of thestudents in both the school and the nursing Council was “Pass” grade. There was a Significant positivecorrelation between the academic performance of third year students and their clinical performance(
Keywords: Academic, Clinical, Method, Performance, Teaching.